Silver(I) complex of 5,6,11,12-tetradehydrodibenzo[a,e]cyclooctene - Hellbach, Björn; Rominger, Frank; Gleiter, Rolf (Journal of organometallic chemistry, 2006)
The reaction of 5,6,11,12-tetradehydrodibenzo[a,e]cyclooctene with silver(I)triflate yielded a 1:2 complex. X-ray investigations revealed that each silver ion is tetrahedrally coordinated to one triple bond and three oxygen atoms of the triflate anion.
Gesehen am 30.10.2020